Benefit finding in renal transplantation and its association with psychological and clinical correlates: A prospective study. Issue 1 (28th November 2018) - de Vries, Alicia M.; Helgeson, Vicki S.; Schulz, Torben; Almansa, Josué; Westerhuis, Ralf; Niesing, Jan; Navis, Gerjan J.; Schroevers, Maya J.; Ranchor, Adelita V.
Abstract : Objectives: The identification of positive psychological changes, including benefit finding (BF), in chronic illness has gained substantial interest. However, less is known about BF in the context of a positive medical intervention. End‐stage renal disease (ESRD) can be regarded as a burdensome condition, but transplantation is expected to restore physical and psychological functioning to a large extent after a period of illness. The aim of this study was to examine (1) changes in BF from pre‐ to 12 months post‐transplantation, (2) the concurrent association of disease‐related characteristics and optimism to BF, and (3) the potential causal relations between BF and distress. Methods: In this longitudinal study, 319 patients completed questionnaires before, 3 months, 6 months, and/or 12 months post‐transplantation. Multilevel models were used for the analyses. Measures included the Illness Cognitions Questionnaire to measure BF, the Life Orientation Test to measure optimism, and the General Health Questionnaire to measure distress. Results: Benefit finding increased from pre‐ to post‐transplantation. Fewer symptoms and comorbidities, and more optimism, were related to more BF over all time‐points. The direction of the relation between BF and distress changed over time. Before transplantation, distress predicted an increase in BF, whereas post‐transplantation, distress predicted a decrease in BF. The causal relation between BF and distress post‐transplantation appeared to be reciprocal. Conclusions: A positive medical intervention such as renal transplantation might facilitate the development of BF. This study indicates the need for longitudinal research on the relation between BF and psychological health in the face of positive events. Statement of contribution What is already known on this subject? Benefit finding refers to the identification of positive psychological changes following a negative life event. Individuals can experience benefit finding following chronic illness. The positive event of kidney transplantation is associated with improvements in patients' physical and psychological functioning. What does this study add? Benefit finding increases from pre‐ to post‐kidney transplantation. Fewer symptoms and comorbidities, and higher optimism are related to more benefit finding. Before transplantation, distress predicts an increase in benefit finding. After transplantation, there appears to be a reciprocal relation between distress and benefit finding such that distress predicts a decrease in benefit finding and benefit finding predicts a decrease in distress.